2000
DOI: 10.1093/oxfordjournals.bja.a013379
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of near-infrared light in the adult human head: implications for clinical near-infrared spectroscopy

Abstract: To test theoretical assumptions supporting the use of near-infrared spectroscopy (NIRS) in clinical practice, we examined the behaviour of NIR light transmission and attenuation in the human head. Sterile probes for emitting and detecting NIR light at a fixed separation of 40 mm were placed in turn on intact skin, skull, dura and cerebral cortex of 10 patients undergoing elective neurosurgery. In the first five patients, the detecting probe was moved through successive extracerebral layers with the emitter on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 1 publication
0
39
0
1
Order By: Relevance
“…23 These have been supported by clinical experimental data, which indicate that cerebral blood flow measured by NIRS is three times greater when the probe is placed on the dura than when it is measured through the scalp.24 More recently, Young et al 25 found that removal of skull bone and dura from the NIRS light path caused a significant reduction in detected intensity (up to 14-fold decrease). These authors suggested that the skull and/or its interface with other layers might act as an optical channel distorting the behaviour of NIRS light in the human head.…”
Section: Discussionmentioning
confidence: 92%
“…23 These have been supported by clinical experimental data, which indicate that cerebral blood flow measured by NIRS is three times greater when the probe is placed on the dura than when it is measured through the scalp.24 More recently, Young et al 25 found that removal of skull bone and dura from the NIRS light path caused a significant reduction in detected intensity (up to 14-fold decrease). These authors suggested that the skull and/or its interface with other layers might act as an optical channel distorting the behaviour of NIRS light in the human head.…”
Section: Discussionmentioning
confidence: 92%
“…It should be noted, however, that estimates of the portion of the path length attributable to cerebral tissue, as opposed to extracerebral tissue, range widely-from 15% to 55%-and the issue is still the subject of some controversy (Young, Germon, Barnett, Manara, & Nelson, 2000). In particular, the fraction of the path length attributable to the adult skull could be substantial (Hueber et al, 2001;Young et al, 2000). Second, it is assumed that the medium being examined with NIRS (e.g., the head) is homogenous.…”
Section: The Modified Beer-lambert Lawmentioning
confidence: 99%
“…Later, Zhao et al (2002) extended these analyses and found that the DPF varied from 6.18 to 7.69 at the forehead, from 7.18 to 8.87 at the somatosensory motor region, and from 6.98 to 9.35 at the occipital region (at 759 nm, with a less than 10% decrease in these values as the wavelength increased to 834 nm). It should be noted, however, that estimates of the portion of the path length attributable to cerebral tissue, as opposed to extracerebral tissue, range widely-from 15% to 55%-and the issue is still the subject of some controversy (Young, Germon, Barnett, Manara, & Nelson, 2000). In particular, the fraction of the path length attributable to the adult skull could be substantial (Hueber et al, 2001;Young et al, 2000).…”
mentioning
confidence: 99%
“…19,20 The skull itself and its interface with other layers in the human head may distort the penetration of near-infrared light by generating an optical channel. 21 In the adult head NIRS is applied in reflectance mode because pterional transmission is not possible. 2,3,14,16,17 The NIRO 300 (Hamamatsu Photonics) measures tissue oxygenation with the use of spatially resolved reflectance spectroscopy.…”
mentioning
confidence: 99%